Development of an ultrasound-imaging procedure and acquisition of ultrasound images of acupuncture points for safety and accuracy of needle insertion - Kim, Sungha (Integr Med Res, 2017)
BACKGROUND: Acupuncture is a relatively safe, commonly used “alternative” medical treatment for various symptoms. However, adverse effects can occur, including trauma, pneumothorax, and central-nervous-system injury. Our objective was to develop a reliable and practical procedure for ultrasound imaging of acupuncture points to improve safety during needling, and to acquire ultrasound images of several (44) acupuncture points, especially those in high-risk areas, according to an in-house standard operating procedure. METHODS: We created the standard operating procedure for ultrasound imaging for acupuncture, and collected ultrasound images of acupuncture points in clinical trials. RESULTS: Ultrasound images for 44 acupuncture points considered as high-risk points were collected from 85 healthy people who were classified by body-mass index, and high-quality, clear representative images of all 44 points were obtained. CONCLUSION: These baseline images could be helpful for understanding the anatomy under the skin at acupuncture points, which would allow for an enhanced safety and more accurate needling.